Peran Teknologi Informasi Dalam Pengembangan Sistem Informasi Akuntansi Sebagai Upaya Peningkatan Kinerja Persediaan Pada Online Shop XYZ - Nadya Andreyanto; Zufi Yustika Magitasiwi; Irda Agustin Kustiwi (FEB Universitas Maritim Semarang, 2024)
This research was conducted at Online Shop XYZ, a medical equipment shop that operates online and utilizes technology such as marketplaces and financial applications such as Jubelio. From the research results, it can be concluded that the Jubelio application has an important role for the inventory accounting information system owned by the XYZ online shop. The jubelio application makes it easier for the XYZ online shop warehouse to maintain its stock, the jubelio application can also improve the performance of the warehouse department. The jubelio application also makes it easier for the XYZ online shop which applies the perpetual method to always monitor its merchandise inventory.